PLANING OF SMALL HYDROPOWER PLANTS AND KEZER RIVER - Fevzi Onen; Mahmut Eminoglu (European Scientific Journal, ESJ, 2013)
Investments of Hydroelectric Power Plants have been grown up and our country has become like a construction site by entering into force of the law concerning the transfer of the right of water use in Turkey since 2001. Turkey has a gross annual hydropotential of 433.000 GWh, which is almost 1% of world total potential. Its share is about 16% of the total hydropower capacity in Europe. This situation has increased the importance of planning and arousing interest of academic levels of hydroelectric power plant (HEP) and small hydropower plant (SHEP). Small-scale micro hydropower is both an efficient and reliable form of energy. The first small hydroelectric plant (SHEP) with a capacity of 88 kW was installed in Turkey in 1902. In this study, a concrete example of a not accumulated hydroelectric facility planning is discussed by aiming of consideration of Kezer River in Turkey hydroelectric energy potential. Finally Installed power and energy values of the total annual flow have been calculated using discharge, net head and turbine efficiency.